A study of food festival loyalty / Zurinawati Mohi - Mohi, Zurinawati (2013)
Food festivals are growing in popularity and warrant in-depth stud-ies of festival visitors. The study of food festivals is now an important and prolific area of tourism research enquiry. The aim of this study is to fill the conceptual gap by examining the interrelationships be-tween festival loyalty and its related constructs, in order to gain an improved understanding of visitors’ loyalty towards food festivals in Macau. The proposed hypothetical modelling the food festival would facilitate further researches into the dynamics of tourism and offer guidelines for practitioners as they constantly strive to provide the best experience for visitors to return or revisit the food festival.